Working Women into the Borderlands - Hernández, Sonia, 1976- (Book collections on Project MUSE., 2014)
In Working Women into the Borderlands, author Sonia Hernández sheds light on how women's labor was shaped by US capital in the northeast region of Mexico and how women's labor activism simultaneously shaped the nature of foreign investment and relations between Mexicans and Americans. As capital investments fueled the growth of heavy industries in cities and ports such as Monterrey and Tampico, women's work complemented and strengthened their male counterparts' labor in industries which were historically male-dominated. As Hernández reveals, women laborers were expected.